Efficacy Of Gallic Acid On Oxytetracycline Induced Neprotoxicity In Rats - K.BALAGANGADHARAN (International Journal of Pharma and Bio Sciences, 2012)
Oxytetracycline (200 mg/kg body weight,ip) was administered in 0.5 ml of sterile physiological saline for 15 days, resulting in significant increase in serum urea, creatinine and reduction in creatinine clearance. A significant increase in lipid peroxidation markers (TBARS and lipid hydroperoxides) and, decrease in enzymic antioxidants (superoxide dismutase,catalase,glutathione peroxidase and glutathione-s-transferase) and non-enzymic antioxidant (vitamin C,vitamin E and reduced glutathione) levels were also observed in oxytetracycline-treated rats. The oral administration of gallic acid (200 mg/kg body weight) attenuated the oxytetracycline induced nephrotoxicity by significantly decreased levels of serum urea and creatininie with the significant normalization of creatinine clearance. Upon the depleted renal antioxidant defense system (enzymic and non-enzymic antioxidants) was significantly increased in rats treated with oxytetracycline. These biochemical observations were supplemented by histopathological examination of kidney section. These results indicate that the antioxidant gallic acid might have a protective role against oxytetracycline induced nephrotoxicity and oxidative stress in rats.